Najważniejsze kierunki, motywy i podstawy konstrukcji wierszy Pirbala Muhammuda - Goran Soran, Ezzadin (My University, 2012)
Pīrbāl Mahmūd is a Kurdish poet from the Kurdistan Region of Iraq. He is one of the most outstanding poetic voices who appeared during the second half of the twentieth century. He composes his poems in Kurdish, Arabic and sometimes in Turkish. However, this academic work is restricted to studying and analyzing the artistic, ideological and literary aspects of his Arabic poems. It sheds light on his life biography and the factors that shaped his creative poetic talent. Pīrbāl Mahmūd’s poems are tackled from the Arabic literary criticism perspective. They are subjected to the criteria of Arabic metrics, rhymes and rhetorical arts due to their Arabic nature. This work, as far as the researcher knows, is the first of its type in tackling Pīrbāl Mahmūd’s Arabic poems in a special academic study.
The Main Trends, Motifs and Structural Bases of Pīrbāl Maḥmūd’s Arabic Poetry
Wydział Neofilologii: Katedra Studiów Azjatyckich
Keywords: literatura współczesna; modern literature; arabski; Arabic; kurdyjski; Kurdish; Pirbal Mahmoud